Job satisfaction, organizational commitment and burnout in teachers in Mexico - Rosalba Treviño Reyes; Jesus-Fabian (OmniaScience, 2023)
The study's objective was to determine the relationships between the proposed variables that impact to the Job Satisfaction, Organizational Commitment and Burnout through the Psychological Empowerment mediator variable. The variables proposed as impact factors were Structural Empowerment and Remunerations for the case of teachers from public middle-higher education institutions in Mexico. The study had a non-experimental design, being a correlational and causal research. The measurement instrument was applied to a sample of 167 teachers, whose data were analyzed using the structural equations method. The findings show which of these direct and indirect effects are generating significant effects. Subsequently, the analysis of the contrast and impact differences between the segmentation groups was proposed: by gender, marital status, schooling and employment status. One limitation was to carry out the cross-sectional study, with the data collected in a single moment. It is recommended to continue with the analysis of Burnout in other contexts and organizational areas.